2021
DOI: 10.1002/ccr3.3774
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 pneumonia in a pediatric sickle cell patient requiring red blood cell exchange

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
(23 reference statements)
0
4
0
Order By: Relevance
“… n/a 0 (0) Teulier et al [ 118 ] France 1 (1/0) 33 HbSS HU (1) BT (1) SCD patient developed severe ARDS secondary to COVID-19 and was successfully treated with anticoagulation and extracorporeal membrane oxygenation; patient did not develop pulmonary arterial hypertension, suggesting different pathophysiology in SCD pts. n/a 0 (0) Walker et al [ 92 ] USA 1 (0/1) 10 HbSS BT (1) Patient developed COVID-19 and ACS requiring red blood cell exchange and remdesivir treatment. n/a 0 (0) Abbreviations : ACS, acute chest syndrome; ARDS, acute respiratory distress syndrome; BT, blood transfusion; CT, computed tomography; DHTR, delayed hemolytic transfusion reaction; h/o, history of; Hosp., hospitalization; HPFH, hereditary persistent fetal hemoglobin; HU, hydroxyurea; ICU, intensive care unit; n/a, not available, not applicable, unknown, or unspecified; pts., patients; NIV, non-invasive ventilation; PICU, pediatric intensive care unit; SCD, sickle cell disease; VOC, vaso-occlusive crisis.…”
Section: Patients With Covid-19 and Sickle Cell Diseasementioning
confidence: 99%
See 2 more Smart Citations
“… n/a 0 (0) Teulier et al [ 118 ] France 1 (1/0) 33 HbSS HU (1) BT (1) SCD patient developed severe ARDS secondary to COVID-19 and was successfully treated with anticoagulation and extracorporeal membrane oxygenation; patient did not develop pulmonary arterial hypertension, suggesting different pathophysiology in SCD pts. n/a 0 (0) Walker et al [ 92 ] USA 1 (0/1) 10 HbSS BT (1) Patient developed COVID-19 and ACS requiring red blood cell exchange and remdesivir treatment. n/a 0 (0) Abbreviations : ACS, acute chest syndrome; ARDS, acute respiratory distress syndrome; BT, blood transfusion; CT, computed tomography; DHTR, delayed hemolytic transfusion reaction; h/o, history of; Hosp., hospitalization; HPFH, hereditary persistent fetal hemoglobin; HU, hydroxyurea; ICU, intensive care unit; n/a, not available, not applicable, unknown, or unspecified; pts., patients; NIV, non-invasive ventilation; PICU, pediatric intensive care unit; SCD, sickle cell disease; VOC, vaso-occlusive crisis.…”
Section: Patients With Covid-19 and Sickle Cell Diseasementioning
confidence: 99%
“…In the general population, children are less likely to experience severe COVID-19 outcomes as compared to adults [ 76 ], but only few studies [ 29 , 72 ] have examined children with SCD and SARS-CoV-2 infection in sufficiently large cohorts from which valid inference can be drawn, as the vast majority of studies were case reports with less than 10 patients [ 67 , 68 , 75 , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] ].…”
Section: Patients With Covid-19 and Sickle Cell Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Still, the overall effect of the coronavirus needs to be elucidated through multicenter reports; the existing reports are mostly speculation rather than ground-level research. Later reports showed that remdesivir injections given with blood transfusion were an effective therapy that does not require immunosuppressive or steroid treatments [163,164].…”
Section: Coronavirus Disease (Sars-cov-2)mentioning
confidence: 99%